2021
DOI: 10.1111/ijcp.14003
|View full text |Cite
|
Sign up to set email alerts
|

Free triiodothyronine to free thyroxine ratio in the differential diagnosis of thyrotoxicosis and hyperthyroidism: A retrospective study

Abstract: Hyperthyroidism is characterised by sustained oversynthesis and release of hormones by the thyroid gland. It most commonly occurs as a result of Graves' disease (GD). 1 A less common cause of thyrotoxicosis is destructive pathologies such as painless thyroiditis, postpartum thyroiditis, and subacute thyroiditis which arise from the destruction of thyroid follicle cells due to autoimmune reaction, infection or drugs. 1 Since GD and destructive thyroiditis (DT) differ in their respective treatment, differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The free T3/free T4 ratio is another useful tool that could have helped us differentiate Graves–Basedow disease from other causes of thyrotoxicosis, since a cutoff point >2.96–3.6 has been established, with a sensitivity of 71% and specificity of 88–99%. However, in our case, the free T3 test was not available at that time ( 17 ).…”
Section: Discussionmentioning
confidence: 91%
“…The free T3/free T4 ratio is another useful tool that could have helped us differentiate Graves–Basedow disease from other causes of thyrotoxicosis, since a cutoff point >2.96–3.6 has been established, with a sensitivity of 71% and specificity of 88–99%. However, in our case, the free T3 test was not available at that time ( 17 ).…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, we have examined RLs for FT3/FT4 ratio as useful parameter to detect thyroid disfunction (35)(36)(37)(38). Some authors have pointed out that this ratio is positively correlated with TSH within the reference range of thyroid function in adults (36).…”
Section: Discussionmentioning
confidence: 99%
“…She had displayed prolonged thyrotoxicosis for 2 years before hospitalization; her clinical course was not typical for destructive thyroiditis, such as subacute thyroiditis and painless thyroiditis. In addition, the FT3/FT4 ratio is lower in destructive thyroiditis than in Graves’ disease, and several studies have shown that the optimal FT3/FT4 ratio cut-off value is 2.8–3.0 [ 5 , 6 ]. In the present case, the FT3/FT4 ratio was elevated at the time of the first diagnosis of overt thyrotoxicosis.…”
Section: Discussionmentioning
confidence: 99%